Karakteristik fisikokimia minuman isotonik air kelapa dengan formulasi penambahan asam sitrat dan NaCl - Khusnul Khotimah Putri Asnia; Maherawati Maherawati; Lucky Hartanti (AGROINTEK, 2024)
Isotonic drinks contain sugar components as a source of energy, minerals to replace the body's electrolytes, and organic acids for body fitness. Isotonic drinks can be made from natural ingredients derived from local foods such as coconut. Coconut water naturally contains minerals such as potassium and sodium. Citric acid is added to meet the pH quality standards of isotonic drinks and enhance the sour taste. The addition of NaCl in this study aims to meet the standard of sodium content in isotonic drinks. This study aimed to determined the characteristics of the best isotonic drink made from coconut water with the addition of citric acid and NaCl formulations. This study used a single-factor Randomized Block Design (RBD), namely the addition of citric acid and NaCl, with three replications. The parameters observed were pH, sodium, potassium, total dissolved solids, plate count, and organoleptic. The data were analyzed using the ANOVA (α=5 %), followed by DMRT (α=5 %). The best treatment was tested using the effectiveness index test. The results showed that adding citric acid and NaCl affected the pH and sodium content. The coconut water isotonic drink has met the SNI for isotonic drinks for pH, sodium, and total dissolved solids. The organoleptic test showed differences in taste parameters and overall preference. The effectiveness index test shows that added 0.30 % citric acid and 0.35 % NaCl is the best coconut water isotonic drink.